Characterization of the microbiota dynamics associated with Moniliophthora roreri, causal agent of cocoa frosty pod rot disease, reveals new viral species - Reyes, Brayan Maudiel Diaz; Fonseca, Paula Luize Camargos; Heming, Neander Marcel; Conceição, Lucas Barbosa de Amorim; Nascimento, Katiucia Ticila de Souza; Gramacho, Karina Peres; Arevalo-Gardini, Enrique; Pirovani, Carlos Priminho; Aguiar, Eric Roberto Guimarães Rocha (Frontiers in Microbiology, 2023)
Theobroma cacao, the cocoa tree, is a target for pathogens, such as fungi from the genera Phytophthora, Moniliophthora, Colletotrichum, Ceratocystis, among others. Some cocoa pathogens are restricted to specific regions of the world, such as the Cacao swollen shoot virus (CSSV) in West African countries, while others are expanding geographically, such as Moniliophthora roreri in the Americas. M. roreri is one of the most threatening cocoa pathogens since it directly attacks the cocoa pods driving a significant reduction in production, and therefore economic losses. Despite its importance, the knowledge about the microenvironment of this pathogen and the cocoa pods is still poorly characterized. Herein we performed RNA sequencing of spores in differential stages of culture in a medium supplemented with cacao pod extract and mycelium collected of the susceptible variety ICT 7121 naturally infected by the pathogen to evaluate the diversity and transcriptional activity of microorganisms associated with the in vitro sporulation of M. roreri. Our data revealed a great variety of fungi and bacteria associated with M. roreri, with an exceptional diversity of individuals from the genus Trichoderma sp. Interestingly, the dynamics of microorganisms from different kingdoms varied proportionally, suggesting they are somehow affected by M. roreri culture time. We also identified three sequences similar to viral genomes from the Narnaviridae family, posteriorly confirmed by phylogenetic analysis as members of the genus Narnavirus. Screening of M. roreri public datasets indicated the virus sequences circulating in samples from Ecuador, suggesting a wide spread of these elements. Of note, we did not identify traces of the viral sequences in the M. roreri genome or DNA sequencing, restricting the possibility of these sequences representing endogenized elements. To the best of our knowledge, this is the first report of viruses infecting the fungus of the genus Moniliophthora and only the third description of viruses that are able to parasite elements from the Marasmiaceae family.